2013
DOI: 10.1088/0957-4484/24/34/345203
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of graphene TE surface plasmons in the terahertz regime

Abstract: Unlike common metals, graphene can support transverse electric (TE) surface modes when the imaginary part of its conductivity is negative. We have theoretically investigated and numerically simulated plasmonic properties of graphene TE surface plasmons (SPs) in the terahertz regime. The influence of the external magnetic field, gate voltage and temperature as the tuning schemes of the SPs have been investigated. The results show that graphene TE modes can be realized by tuning the magnetic fields or gate volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…We found that the frequency dependence of the conductivity of graphene revealed the maxima at resonance suggesting strong plasmonic coupling in agreement with the model described in Refs. [27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…We found that the frequency dependence of the conductivity of graphene revealed the maxima at resonance suggesting strong plasmonic coupling in agreement with the model described in Refs. [27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11] When r g;i < 0, the TM SPPs disappear and, instead, a transverse-electric (TE) surface wave might be present. 7,12,13 In this letter, we predict the existence of a TM SPP mode on graphene, in which the directions of in-plane electron oscillations along two surfaces of graphene are always opposite. As a result, its dispersion equation cannot be directly derived by supposing a graphene interface characterized by the surface conductivity.…”
mentioning
confidence: 94%
“…As a result, its dispersion equation cannot be directly derived by supposing a graphene interface characterized by the surface conductivity. [8][9][10][11][12][13] We also derive the guiding condition of this mode, which is very different from that of conventional TM or TE SPPs on graphene. The presented SPPs are of long propagation distances, but weak mode confinements.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[12][13][14][15][16][17] Moreover, 1-D graphene periodic structures and metallic-dielectric structures have attracted considerable attention in the literature, 18,19 which points out new opportunities in the field of metamaterial, photonic crystal, and surface plasmons. [20][21][22][23] To realizing the concept of true active waveguide, we propose an alternative method by tuning the dielectric property of periodic graphene stack to change the mode propagation constant of electromagnetic (EM) wave. We devise a configuration involving two rows of circular periodic graphene stack cylinders, instead of the metallic hole array and lumped component, so that the proposed SIW can operate over a large tunable range in the THz regime and provide a new platform to integrate all THz devices.…”
Section: Introductionmentioning
confidence: 99%